NEW REVIVALISME ISLAM - Murkilim Murkilim (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2017)
New Islamic revivalism is a contemporary Islamic thought movement that  seeks  to cleanse and  restore the understanding and  practice of Islamic teachings to pure Islam.  New Revivalism  arises  because of the  internal prob- lems  of Muslims and  External and  Western modem influences. New Revivalism  in Pakistan emerged under the  main character of Abul ‘A’la Al-Mawdudi with the idea that the life of Muslims should be governed by Islamic teachings in an Islamic state, which takes the form of “theo democracy”. For the realization of such a state, a gradual Islamic revolution should be undertaken, by first doing the Islamization of society. Hasan Al Bana with Kaffahnya Islamic concept through lkhwanu Muslimin trying to make  it happen by utilizing all available potential, either individually or institutionally, so that Islam becomes a comprehensive, universal ldiology based on the original source; Al-qur’an and Sunnah. The Mus- lim Brotherhood movement became radicalized in the hands of Sayyid Qutub, so ready to conduct jihad  fisabilillah. In Indonesia also found the movement of Revivalism  both in the form of premodernist and  postmodernist among others is padri movement, Muhammadiyah, The United of Islam,  and  in the form of more now among others is Jamaat Islam and Darul Arkam. Keywords: revivalism, Islam